2015
DOI: 10.1371/journal.pone.0117575
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Telomere Shortening and Increasing Chromosomal Instability among PanIN Grades and Normal Ductal Epithelia with and without Cancer in the Pancreas

Abstract: A large body of evidence supports a key role for telomere dysfunction in carcinogenesis due to the induction of chromosomal instability. To study telomere shortening in precancerous pancreatic lesions, we measured telomere lengths using quantitative fluorescence in situ hybridization in the normal pancreatic duct epithelium, pancreatic intraepithelial neoplasias (PanINs), and cancers. The materials employed included surgically resected pancreatic specimens without cancer (n = 33) and with invasive ductal carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 50 publications
(67 reference statements)
5
66
1
Order By: Relevance
“…Intriguingly, the difference between young and middle age was statistically significant, but the difference between middle age and elderly was not significant. Most recently, we have analyzed the telomere dynamics of human pancreatic ductal epithelial cell by tissue Q-FISH (same method of present study) and found that the profile of the telomere attrition was essentially similar to that obtained by previous Southern blotting analysis (Matsuda et al, 2015).…”
Section: Discussionsupporting
confidence: 82%
“…Intriguingly, the difference between young and middle age was statistically significant, but the difference between middle age and elderly was not significant. Most recently, we have analyzed the telomere dynamics of human pancreatic ductal epithelial cell by tissue Q-FISH (same method of present study) and found that the profile of the telomere attrition was essentially similar to that obtained by previous Southern blotting analysis (Matsuda et al, 2015).…”
Section: Discussionsupporting
confidence: 82%
“…Cells in mitosis are often seen in normal tissues exhibiting rapid turnover, such as the epithelium of the gut, but the most important morphologic features of malignancy are atypical and bizarre mitotic igures. In our analysis, 30% of mitosis in pancreatic cancer cells was atypical mitosis, while normal epithelium did not show atypical mitosis and precancerous lesions showed only a few instances of atypical mitosis [9,18].…”
Section: Atypical Mitosismentioning
confidence: 45%
“…Telomeres protect each end of the chromosome from fusion; therefore, telomere dysfunction can be observed as an anaphase bridge [15,17]. A lot of evidence has shown that telomere dysfunction plays a key role in carcinogenesis via induction of CIN [9,27]; thus, detection of an anaphase bridge has been considered a useful method of indirectly evaluating telomere dysfunction and CIN. Multipolar mitosis is metaphase with an abnormal coniguration of the equatorial plate and the chromosomes are located along several radial axes.…”
Section: Atypical Mitosismentioning
confidence: 99%
See 2 more Smart Citations